Tafsir Konstitusional Pelanggaran Pemilukada yang Bersifat Sistematis, Terstruktur dan Masif - M. Mahrus Ali; Irfan Nur Rachman; Winda Wijayanti; Rio Tri Juli Putranto; Titis Anindyajati; Putria Gusti Asih (Jurnal Konstitusi, 2012)
The Constitutional Court has created a legal breakthrough in handling the local head election dispute, in order to uphold the democracy and break     away from habitual practice of systematic, structured, and massive (STM) violations. The Court does not simply calculate the results of vote count but also have to seek the justice and prosecute results counting rate that were disputed. As the juridical normative research, the research uses a statutory, case, historical approach and  the  sociology  of  law.  The  research  shows that throughout 2008-2011 Court has granted the dispute for as many as thirty-two cases. Of that amount  of  cases,  those  with  the  STM  violations are as many as 21 (twenty one) cases. Whereas the nature of TSM were   divided into two kinds namely cumulative and alternative which both may cancel local head election results. There are three types of local head election violations, first, violation  in  the  process  that  does  not  affect  the  results of the election. Second, the breach in the process that affect the election  results, thirdly, violation of the terms of conditions to be a candidate which  are principal in nature and can be measured. The systematic, structured and massive violation of the local head general election is violations committed by the structural apparatus, both government officials and election organizers, collectively; not an individual action, well-planned (by design) and the impact of such offencesis extensive rather than sporadic.